Design and analysis of a variable-speed constant-amplitude wind generator for stand-alone DC power applications - Chen, Hao (2023)
This article presents the design and analysis of a permanent magnet (PM) wind generator, which consists of two sets of windings, and two rotors. The proposed PM wind generator is designed for variable-speed constant-amplitude voltage operation in dc power applications, in order to maximize the utilization of wind energy and make the electricity more accessible to stand-alone situations, e.g., remote areas and offshore islands. The operating principle of the variable-speed constant-amplitude voltage operation of the proposed PM wind generator is demonstrated in detail. A comparative study is carried out among the proposed generator, a conventional surface-mounted PM synchronous generator, and an existing counterpart generator used for the same application. The results show that compared to the conventional PM synchronous generator and the existing counterpart, the proposed PM wind generator exhibits the advantages of high induced voltage, high torque/power density, high efficiency, etc. Finally, the proposed PM wind generator is prototyped and manufactured. The validity of the variable-speed constant-amplitude operation of the proposed generator under both steady-state and dynamic conditions, is verified by experimental results.